Application of Customer Value to Increase Perceived Value through Special Business Request Marketing Program - Simanullang, Lusiana; Marsasi, Endy Gunanto (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
This research was conducted at PT Telkom Indonesia, a company engaged in telecommunications, to evaluate the implementation of the Special Business Request (SBR) marketing program in increasing perceived value by customers. The SBR program is an initiative that offers discounts on large projects to strengthen cooperation with government customers. This research uses a qualitative descriptive method, collecting data from the company through in-depth interviews, observation, documentation, and secondary data. The evaluation was conducted on the effectiveness of the SBR program in increasing customer satisfaction and perceived value, using customer value theory, which emphasizes the difference between the benefits obtained by customers and the costs they incur. The results showed that the SBR program effectively increased customer perceived value, helping PT Telkom Indonesia win significant projects and strengthening long-term relationships with government customers. Recommendations are given to refine the program and introduce more personalized marketing strategies based on individual customer needs to achieve optimal results.